Comparison of May Grunwald Giemsa and Potassium Hydroxide Examination of Malassezia Folliculitis Patient Dermatologic Outpatient Clinic of Dr. Soetomo General Hospital Surabaya - Pramita Ariyanti; Afif Nurul Hidayati; Sunarso Suyoso (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Malassezia folliculitis (MF) is a pilosebaceous follicle infection caused by Malassezia sp., in the form of papules, solid, diameter <1cm, follicular pustules, moderate itchy, in the upper body, and rarely on the face. Microscopic examination with potassium hydroxide (KOH) found spores. May Grunwald Giemsa (MGG) cytologic staining to diagnose MF spores may demonstrate a more detailed and sharper. Objective: Identification of MF with MGG compared KOH in Dermatology outpatient clinic Dr. Soetomo General Hospital. Methods: The study was observational analytic to identify MF using MGG compared KOH. Involving 52 new patients fulfield the criteria of the study from March to May 2016. Results: An examination of 52 patients with MF, 7 patients (13.5%) were negative with KOH examination, while the examination MGG negative in 2 patients (3.8%), but not statistically significant (p ≥ 0.5 ). PPV=90% ; NPV value=100% ; sensitivity=95,7% ; spesificity=28,5% Conclusion: KOH still a good investigation for diagnose of MF, but if clinically result positive MF whereas negative KOH, MGG examination should be performed as a diagnostic confirmation of MF